2009
DOI: 10.2320/matertrans.mer2008371
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Characteristics of UV Photodetector Based on ZnO Nanopillar Thin Films Prepared by Sol-Gel Method

Abstract: ZnO thin films were prepared on a quartz substrate by sol-gel method and a UV photodetector was constructed on the ZnO thin films, with a circular spiral structure in contact with 30 nm IrO 2 electrodes. The ZnO thin films were crystallized at various crystallized temperature (600$700 C) for 1 hour in pure oxygen atmosphere, and were then analyzed by X-ray diffraction (XRD) and the scanning electron microscopy (SEM) to investigate the thin film crystallized structures. From photoluminescence (PL) and I-V measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The as-deposited sol-gel-spin-coat derived ZnO nanostructures have been extensively used for making electronic and optoelectronic devices. Chen et al [10] have reported contrast ratio as nearly 100 at 5 V bias voltage for their ZnO nano-pillar based Schottky contact photodetector fabricated by sol-gel spin coating technique. Yakuphanoglu et al [11] have fabricated and characterized ZnO nanostructure/Si heterojunction for photodetection and photovoltaic applications.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The as-deposited sol-gel-spin-coat derived ZnO nanostructures have been extensively used for making electronic and optoelectronic devices. Chen et al [10] have reported contrast ratio as nearly 100 at 5 V bias voltage for their ZnO nano-pillar based Schottky contact photodetector fabricated by sol-gel spin coating technique. Yakuphanoglu et al [11] have fabricated and characterized ZnO nanostructure/Si heterojunction for photodetection and photovoltaic applications.…”
Section: Introductionmentioning
confidence: 98%
“…These nanostructure-based devices have found wide spread applications in solar cells, gas sensors, memory devices, and ultraviolet photodetectors [7][8][9][10][11][12]. ZnO-based ultraviolet photodetectors have potential advantages that include its strong UV-response, feasibility of simple and low cost processing, and chemical stability even in adverse environment [9][10][11]. Researchers have reportedly used a variety of techniques for growing ZnO nanostructures for fabrication of Schottky contact, MSM, MISIM, heterojunction diodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertically aligned nanostructures on substrates have received increasing attention because of their applications in superhydrophobic surfaces, optoelectronic devices, and chemical‐ or bio‐sensing devices . After revealing that nanostructured vertical arrays could affect cellular response and enhance drug permeation across the cell membrane, nanopillar arrays on substrates have been extensively investigated on cellular studies and intracellular drug delivery .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ZnO thin films can be fabricated using spray pyrolysis, (1) metal organic chemical vapor deposition, (2,3) electron beam evaporation, (4) radio frequency sputtering, (5)(6)(7)(8)(9) thermal oxidation, (10) pulsed laser deposition, (11) molecular beam epitaxy, (12,13) and sol-gel (14)(15)(16) methods. Among these methods, the sol-gel method uses a nonvacuum coating process that features the advantages of simple fabrication and low equipment cost and thus exhibits extremely high market application potential.…”
Section: Introductionmentioning
confidence: 99%